PROGRESSIVE TRENDS IN ROAD SAFETY OF CARGO VEHICLES - Madhuri Deshmukh; Prof S G Joshi (International Journal of Innovations in Engineering Research and Technology, 2021)
Ever increasing number of vehicles on road imposes a due concern about road safety on the automobile manufacturers and the users as well. Cargo vehicle is a major part of automobile sector and attained a new look in the era of internet of things. The current paper presents various modern trends being incorporated in Cargo vehicles to monitor different vehicles and environmental parameters to ensure road safety. Authors have extended the scope of study with due consideration to R&D efforts in advanced sensing, environmental perception and interactive driver assistance systems to avoid road accidents due to uneven/over loading of cargo vehicles in specific. With this kind of challenging efforts, the authors aim to converge important technologies such as automotive-electronics, sensors and mobile communication towards safe operation of cargo vehicles while negotiating the road.